Conventional fluid- and nanofluid-based photovoltaic thermal (PV/T) systems: a techno-economic and environmental analysis. Issue 11 (2nd September 2018) - Hussain, M. Imtiaz; Kim, Jun-Tae
ABSTRACT: In this study, the techno-economic impacts of nanofluids used as coolants to enhance the overall performance of a photovoltaic/thermal PV/T system, in comparison with conventional fluids, are discussed. A transient mathematical analysis was performed to evaluate the technical aspects and energy performance of the PV/T system. The proposed model is used to predict the annual thermal and electrical power outputs of a PV/T system based on CuO nanofluid, Al2O3 nanofluid, and conventional fluids. Economic and environmental analyses of the PV/T systems were performed by taking into account energy payback period, energy production factor, net CO2 mitigation, and net CO2 credit. Because of their greater energy unit area and levelized energy cost, nanofluid based PV/T systems have a lower payback period and better economic savings than those of conventional collectors. Using water, Al2 O3 nanofluid, and CuO nanofluid, the net CO2 mitigation and net CO2 credit are 6.4 tons and 156.8 USD, 6.9 tons and 171.2 USD, and 7.4 tons and 181.6 USD, respectively, for 30 years life of the PV/T system. For typical industrial applications, PV/T systems with nanofluids should be considered as competitors to water-based PV/T collectors.